Peran Kader Posyandu dalam Upaya Pencegahan Stunting pada Ibu Badutadi Kabupaten Tanjung Jabung Timur - Nuralamfajar, Nuralamfajar; Novrikasari, Novrikasari; Astuti, Ika (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
Hindering is a state of inability to flourish in youngsters under five years of age (babies under 5 years of age) which is brought about by tenacious lack of healthy sustenance so the kid is excessively short for his age. Lack of healthy sustenance happens when the child is in the belly and toward the start of the child's introduction to the world, however hindering most actually shows up after the youngster is two years of age. In view of SSGI records for 2021, it is known that in Jambi Territory the most elevated frequency of hindering is in Muaro Jambi Rule (27.2%) and the least is in Jambi City, for East Tanjung Jabung Regime it is 25.6%, better than the benefit of Jambi Area (22.4%). This examination is a quantitative exploration with a sectional methodology. The Geragai District served as the location of the research area. The ideal opportunity for leading the examination was in December 2022 with a populace of 574 moms with Baduta youngsters (old 0-23 months) and an example of 132. A progression of accounts utilizing a poll were then examined univariately, bivariately and multivariately utilizing chi-square. In view of the examination results, there is a connection between the job of posyandu units with a p-worth of 0.000 on forestalling hindering by female youngsters in East Tanjung Jabung Rule in 2022.